2020
DOI: 10.1177/1078155220962178
|View full text |Cite
|
Sign up to set email alerts
|

Drug-related problems in head and neck cancer patients identified by repeated medication reviews on consecutive therapy cycles

Abstract: Background Head and neck cancer (HNC) patients are particularly vulnerable to drug-related problems (DRPs) given the toxicity of concomitant chemoradiotherapy (CCRT). Objective To investigate the number and type of potential DRPs (pDRPs) in HNC outpatients undergoing five consecutive cycles of CCRT. Methods A single-centre, non-randomized, non-interventional, observational study was conducted at the Oncological Outpatient Clinic of the Center for Integrated Oncology at the University Hospital Bonn, Germany. Cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…This number was lower, compared to a retrospective study by Vucur et al on head and neck cancer outpatients. DRPs per patient ranged from 4.8 (first therapy cycle) to 6.9 (fifth therapy cycle) [ 19 ]. However, our findings correspond to the studies of Nightingale et al and Tan et al, with three DRPs per patient, and Edwards et al, showing 3.7 DRPs per patient [ 6 , 18 , 20 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This number was lower, compared to a retrospective study by Vucur et al on head and neck cancer outpatients. DRPs per patient ranged from 4.8 (first therapy cycle) to 6.9 (fifth therapy cycle) [ 19 ]. However, our findings correspond to the studies of Nightingale et al and Tan et al, with three DRPs per patient, and Edwards et al, showing 3.7 DRPs per patient [ 6 , 18 , 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, every administered drug can cause a DRP. The number of drugs per patient corresponds to the findings of most comparable studies [6,18,19], which is also true for the number of patients with polymedication. In contrast, the number of patients with hyperpolymedication is slightly higher in this study [3,6,7].…”
Section: Medication Risksmentioning
confidence: 93%
See 1 more Smart Citation
“…Pharmacists’ positive contribution to multidisciplinary collaboration in oncology has been confirmed by numerous studies, which have demonstrated the benefits of pharmaceutical consultation in both outpatient and inpatient settings for various tumor entities. 3237…”
Section: Discussionmentioning
confidence: 99%
“…Pharmacists' positive contribution to multidisciplinary collaboration in oncology has been confirmed by numerous studies, which have demonstrated the benefits of pharmaceutical consultation in both outpatient and inpatient settings for various tumor entities. [32][33][34][35][36][37] Especially in high-risk processes, not only the four-eyes principle is widely established: with the introduction of different checkpoints at different points of the process by different staff members, potential errors are detected at an early stage so that they do not reach the patient in the first place. These safety barriers do not necessarily have to be ensured by employees but can also relate to standardized processes or materials used.…”
Section: Categories Of Errors Frequency Examplementioning
confidence: 99%